Uji Aktivitas Antioksidan Kombinasi Ekstrak Sarang Semut ( Myrmecodia Pendans) dan Daun Sirsak (Annona muricata) dengan Metode DPPH (2,2-diphenyl-1-picrilhidrazyl) - Wimpy; Suharyanto (Jurnal Farmasi (Journal of Pharmacy), 2014)
Free radicals are highly reactive molecules containing one or more unpaired electrons in its outer orbital Free radicals attackelectron binding molecules in the surrounding areas. Malfunctioning cells, damage cell structures, and even mutations are the effects of free radical. Antioxidants can inhibit reactive oxygen and free radicals in the human body. The compound flavonoid, which is contained in thesoursop’s leaf and sarang semut act as anti-oxidants. This researchaimsto test the antioxidant activity of the combination of extracted sarang semut (Myrmecodia pendans) and Soursop’s leaf (Annona muricata) with DPPH (2,2-diphenyl-1-picrilhidrazyl) method. This researchwas conducted by plant extraction Sarang semut and soursop’s leaf with maceration The results showed that ultrasonic extraction techniqueall fractions are detected such as alkaloids, flavonoids, saponins and tannins, water fraction of sarang semut has76.64 ppm IC50 and the butanol fractions has 76.82 ppm IC50, the combination of extracted sarang semut and extracted soursop’s leaf (1: 1) have 71.09 ppm IC50, the water fraction soursop leafhas 73.48 ppm IC50, and butanol fraction has 99.70 ppm so we can conclude that the water fraction of sarang semut is better than butanol fraction of sarang semut extract. The combination between extracted soursop’sleaf and extracted sarang semut with a ratio of 1: 1 has a better antioxidant activity than the singular.